2020
DOI: 10.3390/metabo10090349
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Biomarkers in the Cervicovaginal Fluid by Metabolic Profiling for Preterm Birth

Abstract: During pregnancy, dysbiosis in the vaginal microbiota directly affects the metabolic profiles, which might impact preterm birth (PTB). In this study, we performed cervicovaginal fluid (CVF) metabolic profiling using nuclear magnetic resonance (NMR) spectroscopy and identified the metabolic markers for predicting PTB. In this nested case-control study, 43 South Korean pregnant women with PTB (n = 22), and term birth (TB; n = 21) were enrolled with their demographic profiles, and CVF samples were collected by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 56 publications
1
26
0
Order By: Relevance
“…We did not distinguish between L-and D-lactate due to use of the NMR platform. Expanding the range of metabolites using mass spectrometry would be desirable (52) although through CVF NMR analysis we identified 29 metabolites which are comparable to previous NMR studies (i.e., six (42), 11 (46) and 28 (44)).…”
Section: Developing Sptb Models Using Species-level Phylotypes Metabolites and Hdpssupporting
confidence: 77%
“…We did not distinguish between L-and D-lactate due to use of the NMR platform. Expanding the range of metabolites using mass spectrometry would be desirable (52) although through CVF NMR analysis we identified 29 metabolites which are comparable to previous NMR studies (i.e., six (42), 11 (46) and 28 (44)).…”
Section: Developing Sptb Models Using Species-level Phylotypes Metabolites and Hdpssupporting
confidence: 77%
“…The importance of deciphering the vaginal metabolic profiles lies in the fact that the composition of vaginal metabolome can significantly impact on maternal-foetal health [ 36 ]. It has been shown that specific vaginal molecules (e.g., acetone, ethylene glycol, formate, glycolate, isopropanol, methanol, and TMAO) can predict the risk of preterm birth, with a negative correlation with gestational age at birth and cervical length [ 24 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…While many studies have investigated the composition of the vaginal microbiome during pregnancy, less information is available regarding the vaginal metabolome in the different periods of gestation [ 22 24 ]. Therefore, in this study we characterized and compared the vaginal metabolomic profiles throughout pregnancy at two different gestational ages (i.e., first and second trimester), correlating them with a microscopic evaluation of the vaginal bacterial composition and various clinical and demographic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the bacterial communities are accompanied by profound alterations in the composition of vaginal metabolites: specific vaginal molecules (e.g., acetone, ethylene glycol, formate, isopropanol, and methanol) can predict the risk of preterm birth, with a negative correlation with gestational age at birth (Ghartey et al, 2015;Ansari et al, 2020).…”
Section: Introductionmentioning
confidence: 99%